2021
DOI: 10.3390/polym13183092
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Chain-Extending Cross-Linkers on the Mechanical and Thermal Properties of Poly(butylene adipate terephthalate)/Poly(lactic acid) Blown Films

Abstract: This study investigates the effects of four multifunctional chain-extending cross-linkers (CECL) on the processability, mechanical performance, and structure of polybutylene adipate terephthalate (PBAT) and polylactic acid (PLA) blends produced using film blowing technology. The newly developed reference compound (M·VERA® B5029) and the CECL modified blends are characterized with respect to the initial properties and the corresponding properties after aging at 50 °C for 1 and 2 months. The tensile strength, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…Due to the blown film extrusion with different draw ratios in ED and TD, anisotropic mechanical properties and corresponding differences in a morphological structure may be expected. Recently, Azevedo et al [ 28 ] showed (based on differential scanning calorimetry data of granules and films) that the chemical reactions were incomplete after compounding and that blown film extrusion intensified them even for rapidly cooled 25 µm films. This behavior can be explained by assuming that the CECL molecules are linked with one reactive site to polymer chains during compounding, whereas the other reactive sites remain unaffected.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the blown film extrusion with different draw ratios in ED and TD, anisotropic mechanical properties and corresponding differences in a morphological structure may be expected. Recently, Azevedo et al [ 28 ] showed (based on differential scanning calorimetry data of granules and films) that the chemical reactions were incomplete after compounding and that blown film extrusion intensified them even for rapidly cooled 25 µm films. This behavior can be explained by assuming that the CECL molecules are linked with one reactive site to polymer chains during compounding, whereas the other reactive sites remain unaffected.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, chain scission and cross-linking altered viscosity and consequently the structure, e.g., dimensions of the dispersed phase and its geometry (spherical or fibrillar). According to dynamic mechanical analysis [ 28 ], for V1 CECLs, the T g of PLA and PBAT phases were hardly affected, whereas for V2 to V4, an increase of T g in the PBAT phase and a decrease in the PLA phase were observed. This means that cross-linking mainly occurred in the PBAT phase, whereas in the PLA phase, the free volume was mainly increased by partial reaction with CECL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Promising results were obtained by the blending with poly(butylene-adipate-co-terephthalate) (PBAT), an aliphatic aromatic copolyester characterized by a good processability and mechanical properties quite similar to polyethylene, i.e., low elastic modulus and high ductility, [ 19 , 20 ]. Although PBAT is inherently not compatible with PLA, the two resins can be effectively compatibilized in situ by reactive extrusion, obtaining blends more suitable for the film blowing process [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. However, despite the numerous studies focused on production and characterization of blown films from PLA/PBAT blends, there is very little information on their use for development of shrink films by film blowing, and only reported in patent literature [ 28 , 29 ], therefore further investigations are needed.…”
Section: Introductionmentioning
confidence: 99%
“…This problem has created the need for materials that have greater stability against environmental stresses. To resolve this issue, the fabrication of polymeric nanocomposites is under consideration, and especially the usage of inorganic nanofillers, which not only provide greater stability against the environment, but also enhance their electrical and dielectric properties [3][4][5]. Different morphologies of nanofiller are being explored to achieve a greater interface area.…”
Section: Introductionmentioning
confidence: 99%